ANTESEDEN ATTITUDE TOWARDS M-BANKING DAN DAMPAKNYA TERHADAP BEHAVIORAL INTENTION TO ADOPT M-BANKING - Titon Adrinanto (Jurnal Manajemen dan Pemasaran Jasa, 2015)
The background of this research was mbanking users in Indonesia is still low despite the mobile phone users in developed and developing countries in the world has increased rapidly since 21st century. Some bank companies in Indonesia has been offering mbanking service but the use of mbanking for financial transaction is still low and limited. The objectives of this research was to analyze the antecedents of attitude towards mbanking and its impact on behavioral intention to adopt mbanking.The design of this research applies hypothesis testing. 200 samples selectedfrom prospective user of 3 government bank. The sampling technique was purposive sampling with crosssectional study. Data analysis used in this research was collected by questionnaire technique with item of statements for each variable. In order to obtain valid and reliable instrument tool, validity and reliability test has been done. The result of this research conclude that there is positive effect perceived usefulness, perceived ease of use, perceived competence, perceivedcommunication, perceived privacy and security, society influence, and facilitating condition on attitude towards mbanking.This study supports that there is positive influence on attitude towards mbankingon behavioral intention to adopt mbanking.